Enhancing Performance of Student in Web Programming using Digital Educational Comics - Zaibon, Syamsul Bahrin; Azman, Farah Nadia; Shiratuddin, Norshuhada (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
With the increasing demand for web developers when current and future applications are stored and accessed through the World Wide Web (WWW), web programming has become a highly rewarding career for ICT students. Hence, educators in higher education need to apply effective method in teaching web programming skills. In web programming course, retaining students’ engagement due to the breadth and depth of web technology remains as one of the classroom challenges. This caused students to convey disinterest and negative attitude toward web programming subject and resulted with low performance. Therefore, this study aims to improve performance of students by implementing digital educational comics as a teaching reflection tool for the subject. An experimental study was conducted, and the findings reveal that the experimental group performs better than the controlled group in overall academic performance and pre-post test results.